Avaliação da biodisponibilidade de metais em amostras de sedimentos do Rio Uberabinha (Uberlândia Minas Gerais) - Silva, Luciano Alves da (2009)
The increase in human activities such as industrialization and, urbanization is responsible for an high disposal of toxic metals in water bodies. These activities are responsible for the introduction of significant quantities of toxic elements in natural waters adversely affecting the quality of sediments. The sediments can accumulated hazardous substances, or act as a secondary source of pollution through the releasing of contaminants in aquatic systems. Such behavior can be dangerous to the environment and human health. The goal of this study was to determine the total concentration and bioavailability of some elements considered toxic to the environment and human health such as Cd, Pb, Cu, Cr and Zn in sediments collected in different parts of the river Uberabinha (Uberlândia, MG). For this purpose, the sequential chemical extraction method proposed by Standards, Measurements and Testing Programs (Community Bureau of References - BCR) was applied. In this method, the metals are extracted from fractions of carbonates, iron, manganese and aluminum oxides and the fraction bound to organic matter. Additionally, other step "pseudototal" is recommended. This step is used to evaluate the metal boudend to some silicates and primary minerals. The metals were determined by flame atomic absorption spectrometry (FAAS). The metals extracted were: cadmium, chromium, copper, zinc and lead. For data comparison samples of sediments were decomposed intocavits microwave oven, and subsequently the metals were also determined by flame at abs spec (FAAS). The results allowed to evaluate the quality of sediments in the Rio Uberabinha and the potential mobility and toxicity of these elements. Affer the proposed study it is able to evaluate the bioavailability of toxic metals and, consequently, provides the risk of the environment. The results show that the five points to collect the amount of metal found in the sediment was not significant. Lead was an exception, as mentioned above the values presented by the CONAMA resolution.